Changes in the Parent Cystic Fibrosis Questionnaire-Revised (CFQ-R) with respiratory symptoms in preschool children with cystic fibrosis - Perrem, Lucy (J Cyst Fibros, 2020)
INTRODUCTION: The Cystic Fibrosis Questionnaire-Revised (CFQ-R) Respiratory score is a validated and widely used patient-reported outcome. This study aimed to establish changes in the score with acute respiratory events in preschool children with CF and to investigate its’ relationship with physiological outcomes. METHODS: The Parent CFQ-R, multiple breath washout test and spirometry were performed at six study visits over one year. The clinical status of participants, stable or symptomatic, was defined by the patient’s physician. Linear regression and distribution-based statistical methods were used to examine the changes in the CFQ-R from the last stable visit and to investigate its relationship with physiological outcomes. RESULTS: There were 272 stable and 115 symptomatic visits from 78 participants. The mean CFQ-R Respiratory score did not change between consecutive stable visits (−0.73, SD 20.4). The mean (SD) score deteriorated by 15.5 (20.7) points between stable and symptomatic visits and improved by 14.8 (20.1) points between symptomatic and stable follow-up visits. When a clinically important change is defined as 0.5SD change (10-points), the positive predictive value (PPV) was 45% and the negative predictive value (NPV) was 84%. For visits with a 10-point worsening in the CFQ-R Respiratory score and a 15% increase in LCI, the PPV was better (81%) than using either measure alone. CONCLUSION: The CFQ-R Respiratory score is responsive to acute respiratory events in preschool children with CF and its utility to monitor individual patients is improved when combined with LCI.